Tuning of the bandgap of Rb2ScAgX6 (X = Cl, Br, I) double perovskites through halide ion replacement for solar cell applications. (September 2022) - Asghar, Mazia; Zanib, Maiza; Khan, M. Aslam; Niaz, Shanawer; Noor, N.A.; Dahshan, A.
Abstract: Double perovskite halides are a potential candidate for the applications of the solar cell, photovoltaic and thermoelectric, due to their non-toxicity and environmental stability. The density functional theory (DFT) calculation investigates the details physical properties of halides Rb2 ScAgX6 (X = Cl, Br, I) that can be useful for applications like thermoelectric and solar cells. The structural and thermodynamics stability is endorsed by the formation energy, tolerance factor, and Born stability criteria. The calculated indirect band gaps of 1.95 eV, 1.85, and 1.60 eV for Rb2 ScAgCl6, Rb2 ScAgBr6, and Rb2 ScAgI6 respectively, ensure the light absorption in the region of visible range. Therefore, all studied halides are widely used in optoelectronic devices like solar cells. In addition, thermoelectric properties are examined through thermal conductivity, electrical conductivity, and the Seebeck coefficient. ZT values of 0.74, 0.71, and 0.72 for Rb2 ScAgI6, Rb2 ScAgBr6, and Rb2 ScAgCl6 double perovskites are recorded, which spotlight their significance for the applications of thermoelectric.